An on‐site alert level early warning system for Italy. Issue 3 (11th March 2017) - Caruso, A.; Colombelli, S.; Elia, L.; Picozzi, M.; Zollo, A.
Abstract: An earthquake early warning (EEW) system is a real‐time seismic monitoring infrastructure that has the capability to provide warnings to target cities before the arrival of the strongest shaking waves. In order to provide a rapid alert when targets are very close to the epicenter of the events, we developed an on‐site EEW approach and evaluated its performance at the Italian national scale. The system is a P wave‐based method that measures in real time two parameters: the initial peak displacement ( Pd ) and the average period ( τ c ). As output, the system provides the predicted ground‐shaking intensity at the monitored site, the alert level, and a qualitative classification of both earthquake magnitude and source‐to‐receiver distance. We applied the on‐site EEW methodology to a data set of Italian earthquakes, with magnitude ranging from 3.8 to 6, and evaluated the performance of the system in terms of correct warning and lead times (i.e., time available for security actions at the target). The results of this retrospective analysis show that for the large majority of the analyzed cases, the method is able to deliver a correct warning shortly after the P wave detection, with more than 80% of successful intensity predictions at the target site. The lead times increase with distance, with a value of 8–10 s at 50 km and 15–18 s at 100 km. Key Points: We develop and validate a new on‐site early warning method suitable for regions monitored by dense strong motion arrays such as Italy Alert is based on the real‐time, evolutionary measure of the P wave amplitude and period, as acquired by one or few more co‐located sensors The method shows a high percentage of successful intensity predictions and allows to reduce the blind zone extent of network‐based EWS